2008
DOI: 10.1182/blood-2008-07-169342
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus is associated with veno-occlusive disease of the liver after myeloablative allogeneic stem cell transplantation

Abstract: Sirolimus is an effective agent used in graft-versus-host disease (GVHD) prophylaxis after allogeneic transplantation. It also has antiproliferative effects on vascular endothelium when used to coat coronary artery stents. We noted an excess of veno-occlusive disease (VOD) in a clinical trial, and retrospectively reviewed the records of 488 patients to determine the association between sirolimus and VOD. When used with cyclophosphamide/total body irradiation (Cy/TBI) conditioning, sirolimus is associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(109 citation statements)
references
References 49 publications
5
101
3
Order By: Relevance
“…In contrast to previously published evidence in the setting of busulfan/cyclophosphamide conditioning, 27 or that of largely intravenous busulfan/fludarabine but with the combination of TAC/everolimus, 29 we did not observe a significantly increased risk of hepatic VOD among patients treated with SIR/TAC and busulfan-based conditioning. However, the overall incidence of this complication was low and this risk was likely mitigated by avoiding cyclophosphamide, pharmacokinetic targeting of intravenous busulfan, initiation of SIR on day -1 after conditioning therapy was completed, and VOD prophylaxis with ursodeoxycholic acid in all patients.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In contrast to previously published evidence in the setting of busulfan/cyclophosphamide conditioning, 27 or that of largely intravenous busulfan/fludarabine but with the combination of TAC/everolimus, 29 we did not observe a significantly increased risk of hepatic VOD among patients treated with SIR/TAC and busulfan-based conditioning. However, the overall incidence of this complication was low and this risk was likely mitigated by avoiding cyclophosphamide, pharmacokinetic targeting of intravenous busulfan, initiation of SIR on day -1 after conditioning therapy was completed, and VOD prophylaxis with ursodeoxycholic acid in all patients.…”
Section: Discussioncontrasting
confidence: 56%
“…Notably, the incidence of VOD observed in this study is lower than that previously reported. 27 The cumulative incidence of TMA did not differ significantly between the two groups [SIR/TAC 25% (95% CI: 14-44%) versus MTX/TAC 20% (95% CI: 10-38%)] (P=0.48). TMA occurred in nine SIR/TAC-treated patients and seven MTX/TAC-treated patients (P=0.57).…”
Section: Engraftment and Early Toxicitymentioning
confidence: 99%
“…24,25 The efficacy of sirolimus has been demonstrated in solid organ transplantation, but a definite role in allogeneic HCT has yet to be defined. In the setting of high-dose conditioning, the addition of sirolimus to calcineurin-based acute GvHD prophylaxis has been associated with lower levels of acute GvHD compared to historical data.…”
Section: Cumulative Incidence (%) Hr (95% Ci); Pmentioning
confidence: 99%
“…One of the major problems with sirolimus is its toxicity profile in combination with calcineurin inhibitors, including the development of microangiopathy or veno-occlusive disease, especially among patients receiving myeloablative conditionings. 33,34 We have previously reported that bortezomib induces selective depletion of alloreactive T cells, 25 while Treg are resistant to this pro-apoptotic effect. Furthermore, bortezomib allows the expansion of a suppressive T-cell subpopulation in vitro.…”
Section: Discussionmentioning
confidence: 99%